Baited videos to assess semi-aquatic mammals: occurrence of the neotropical otter Lontra longicaudis (Carnivora: Mustelidae) in a marine coastal island in São Paulo, Southeast Brazil - Rolim, Fernanda Andreoli [UNESP]; Rodrigues, Pedro Furtado Costa [UNESP]; Gadig, Otto Bismarck Fazzano [UNESP] (Springer Nature, 2018)
A new record of the neotropical otter (Lontra longicaudis) in the marine environment near the rocky reef of a coastal island in Brazil is described here, being the first published report of a semi-aquatic mammal by baited remote underwater video system. This species is not usually sighted in marine waters away from the mainland coast, and it has never been reported in this environment in this region. This individual may have increased its feeding grounds further offshore as food resources close to the mainland are reduced. Baited videos present a relatively low cost option to understand better these animals existing in different habitats, improving the monitoring for these species and providing valuable information on their distribution, habitat use, and life history.
Keywords: BRUV; Estuaries; Mammalia; Southwestern Atlantic